Estrategias de gestión del patrimonio cultural en los GAD: caso Cantón Urcuquí 2013 – 2014 - Bolaños Alomoto, Carlos Darwin (2014)
The emphasis that the current government has given to the heritage is a highlight, the Constitution of the Republic of Ecuador (2008), marks a starting point in relation to the concept of development, which is privileged humans, leaving a smallest mercantilist concept of economic development. In this line the heritage becomes an important dimension, therefore, it is necessary to know the laws generated by the State for management and empowerment in the territory. This study takes a tour around the legal framework created by the State to the heritage sector and analyzes the applicability Autonomous Decentralized Governments that have the same, and recommended for the canton Urcuquí, institutional capacities and management methodologies heritage should generate to allow him to execute these state policies into effective action on its territory.